Queering the gothic - Hughes, William, 1964-; Smith, Andrew, 1964- (Manchester Gothic (Manchester, England)., 2017)
A first rate collection of essays on queer Gothic, ranging from 'Frankenstein' to George Eliot, E.M.Forster to Michael Jackson. Provides a chronological investigation of the Gothic from the eighteenth century to the present day and in doing so produces a new way of reading the Gothic tradition.